Profil Kompetensi Pedagogik dan Profesional Mahasiswa Calon Guru Fisika - Fatma Hamid; Saprudin Saprudin (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2020)
This research is a survei that aims to describe the profile of pre-service physics teachers (PPT)' pedagogical and professional competencies. This survei was involved 60 PPT for the sixth semester to eighth semester on the 2015-2016 academic year in the physics education study program at a LPTK in Ternate, Indonesia. Data was collected through teacher competency tests and documentation studies. The results of the data analysis showed that the PPT' pedagogical and professional competencies can be categorized as low with a percentage of 34.0% and 25.8%. The results of this survei are expected to be used as a reference in formulating appropriate actions related to improving the PPT' pedagogical and professional competencies at the research location.